TATA LAKU SISWA TERHADAP GURU DALAM LONTAR SILAKRAMANING AGURON-GURON - Anak Agung Gde Krisna Paramita; Dewa Ayu Kade Linda Dewi (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2022)
This research focuses on the study of student behavior towards teachers in the lontar text of Sila Kramaning Aguron-guron. This research method is in the form of qualitative which discusses the ethics of student behavior towards teachers as contained in the lontar sila kramaning aguron-guron. This research is a description of the teachings of etiquette contained in the lontar Sila Kramaning Aguron-guron on sheet 1b and analyzes the aspects of the teaching. Also, a student must be devoted to the teacher, which is related to the teachings of the teacher of devotional service, the lightest is always on the right behavior, right speech and a mind that is not defiled, namely the teachings of Tri Kaya Parisudha, students have self-control and are directed to the good to free themselves from the bondage of the senses. The behavior in question is that students are able to have ethics towards teachers who provide education.